Small And Medium Island Chalet Operators In Selected Islands Of Terengganu And Pahang - Maideen, Siti Aishah (2010)
In Malaysia, the tourism industry is one of the important sectors contributing to the national growth. The number of tourist arrivals in Malaysia increased from 13.3 million to 23.6 million in 2009. This has led to the establishment of many small and medium hotels, resorts and chalets in Malaysia. In the East Coast of Peninsular Malaysia, the islands facing the South China Sea cannot operate all year round due to the monsoon season. This study examines the small and medium island chalet (SMIC) operators in four islands, namely Kapas Island, Perhentian Island, and Redang Island in Terengganu and Tioman Island in Pahang. Specifically, it focused on the demographic profiles and entrepreneur characteristics, profile of the premises, management and operational aspect of the premises, their Critical Success Factors (CSFs) and challenges that the premises faced. This study used the multimethods approach, comprising quantitative and qualitative methods.